Religious Protection of Children in Polygamic Families in Langkat Regency Based on Law Number 35 of 2014 Concerning Child Protection - Titi Susanti; Ramadhan Syahmedi; Hafsah Hafsah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
There are the forms of attention to children's religious values that cannot be implemented properly in polygamous families in Langkat Regency. Responding to the polygamy cases in Langkat Regency, this is an interesting phenomenon to study regarding the protection of the child's religion in the family. This study was field research, with its approach normative. religious protection for children based on Law number 35 of 2014 in several articles, namely articles 6, 25, 26, 39 and 43. The impact on child victims of polygamy who do not receive religious protection in Langkat Regency is that the child is psychologically disturbed. Never again did he hear calls or invitations to pray in congregation, recite the Koran or the advice he had received from his parents. Plus, friends who lack good morals. So that children often find their solutions to all the problems they face. Children become misdirected due to promiscuity and experience depression, so few are trapped in the diseased environment of society. So that children often find their solutions to all the problems they face. Children become misdirected due to promiscuity and experience depression, so few are trapped in the diseased environment of society. However, not all children who are victims of polygamy at this level become wrong associations. There are also those whose personality is getting better. Because attention from his father is still given, although not like before, his mother at home is also protective of his association. The surrounding community and religious leaders also play a role in embracing him so that he remains in an association that brings benefit